2019
DOI: 10.1093/jas/skz126
|View full text |Cite
|
Sign up to set email alerts
|

Growth, health, rumen fermentation, and bacterial community of Holstein calves fed Lactobacillus rhamnosus GG during the preweaning stage1

Abstract: The aim of this study was to determine if feeding Lactobacillus rhamnosus GG (GG, ATCC 53013) to neonatal calves would alter their growth, health, rumen fermentation, and bacterial community composition during the preweaning stage; we hypothesized that it would. Twenty-four male Holstein calves were blocked and randomly assigned to 1 of 2 treatment groups: 1) untreated control (CON), or 2) treated with 1 × 10 10 cfu/d of a GG suspension (GG). Calves received GG daily, mixed with the milk replacer in the mornin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 56 publications
5
21
0
Order By: Relevance
“…Probiotics can produce amylase, cellulase, protease and other substances, which will improve the digestive function of calves and promote their growth [ 21 ]. Previous studies have shown that the probiotics can promote the growth of experiencing high incidences of diarrhea calves [ 22 , 23 ], which was similar to our results.…”
Section: Discussionsupporting
confidence: 93%
“…Probiotics can produce amylase, cellulase, protease and other substances, which will improve the digestive function of calves and promote their growth [ 21 ]. Previous studies have shown that the probiotics can promote the growth of experiencing high incidences of diarrhea calves [ 22 , 23 ], which was similar to our results.…”
Section: Discussionsupporting
confidence: 93%
“…However, feeding gallic acid did not affect the acetate to propionate ratio in the current study. A previous study also found that starter intake and VFA production increased and pH decreased in preweaning calves (Zhang et al, 2019). The decreased pH could be attributed to the increase in calf starter intake, and the comprehensive improvement in health status and development of gastrointestinal tract might contribute to increased starter intake in the present study.…”
Section: Ruminal Fermentationsupporting
confidence: 74%
“…Specifically, yeast supplementation during the preweaning period has been associated with a reduced incidence and severity of diarrhea in male dairy calves and calves raised for veal (88,89), especially male calves with failed transfer of passive immunity (90). Supplementation with lactic acid bacteria has also been shown to reduce the risk of diarrhea [reviewed by (91)], particularly when male calves experienced high incidences of diarrhea (92,93). There are, however, inconsistent results with supplementation (87), suggesting that other management practices may be important to consider.…”
Section: Nutritional Strategiesmentioning
confidence: 99%